The Influence Of Leadership, Emotional Intelligence And Competence On Employee Performance: Systematic Literature Riview - Ulandari, Novy Dian Tri; Nilam, Nur; Andika, Andika; Syarifah Nur Azzahra; Wardhana, Mada Aditia (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2025)
This study aims to examine the trends and developments in the literature concerning the influence of leadership, emotional intelligence, and competence on employee performance during the 2020–2025 period using a Systematic Literature Review (SLR) approach. By analyzing 808 articles through Latent Dirichlet Allocation (LDA), the study found that the core topic of these three variables dominated academic attention, peaking in 2024. Although a decline in interest occurred in 2025, projections through 2028 indicate renewed growth. The findings highlight the need for interdisciplinary approaches, contextual exploration, and the development of integrative theoretical models to better understand the dynamic relationships among the variables. Practical implications include the use of analytic technologies and stronger collaboration between academics and practitioners in formulating more adaptive human resource strategies.